Security Quality Measurement Based on ISO/IEC 25023 Quality Model Case Study: Hospital Management Information System - Taniasari, Nungky; Shodikin, Mohamad (Journal La Multiapp, 2024)
Hospitals need to protect the security of data assets, where data assets are an important part of the continuity of hospital operations. In connection with the protection of data and information assets in the hospital, it has become a requirement for the hospital information technology team to carry out a security audit of the hospital management information system (HMIS). In this study, we measured the quality of the HMIS software in X Hospital using ISO 25023 which focused on the security aspects of the outpatient service module and drug services in the outpatient pharmacy unit. The security aspect based on the ISO 25023 standard consists of five main characteristics, namely: confidentiality, integrity, non-repudiation, accountability and authenticity. In the early stages, calculations are carried out to find the value of each measurement standard which is denoted by (X). The X value is based on the standard calculation range of values 0 and 1. The threshold value is determined at 0.80 to categorize the point quality whether it is not good or has met the ISO 25023 quality point. The results of software quality measurements show Internal Data Corruption Prevention is worth 0.75 and is at below a predetermined threshold value. Based on these results, it is recommended to improve one of them by replication the database to minimize the possibility of Internal Data Corruption Prevention. In this study, all aspects of software quality have an average value above the threshold, so it can be concluded that HMIS in RS X meets ISO 25023 standards.